The Role of Sharia Bank Digital Services in Improving Sharia Financial Literacy (A Literature Review) - Trimulato, Trimulato; Mustamin, Asyraf (Maqrizi: Journal of Economics and Islamic Economics, 2025)
Digital transformation in the financial sector has brought significant changes to the way people access banking services, including in the context of Islamic banks. However, the acceleration of digitalization has not been fully balanced with the increasing Islamic financial literacy of the people. This study aims to evaluate and map the relationship between Islamic bank digital services and increasing Islamic financial literacy. This study employs the Systematic Literature Review (SLR) approach, incorporating a bibliometric method. This type of research is qualitative, with secondary data obtained from 105 scientific articles indexed by Google Scholar during the period 2018–2024. The data collection technique was carried out through the Publish or Perish (PoP) application, while the analysis was carried out using the VOSviewer software to map the network of keywords, research trends, and author collaboration. The results show a significant increase in the number of publications since 2021, with the main focus on the integration of digital services and Islamic financial literacy. Keywords such as "literacy," "Islamic banks," and "digital services" emerged as dominant thematic centers. Even so, collaboration between researchers is still limited and tends to be fragmented. The policy implications of these findings encourage the need to strengthen synergy between Islamic financial institutions, the government, and academics in designing digital services that also function as educational instruments. Thus, the development of digital technology in Islamic banking is not only a tool for transaction efficiency, but also a strategy to strengthen the foundation of Islamic financial literacy sustainably. The limitations of this study are in the period of research data presented, so that more can be made.